Association of Maternal Body Mass Index With Risk of Infant Mortality: A Dose-Response Meta-Analysis - Huo, Nana; Zhang, Kun; Wang, Li; Wang, Lina; Lv, Wenhui; Cheng, Wenke; Jia, GuangZhu (Frontiers in Pediatrics, 2021)
Abstract Objective: we presumed that a high or low BMI might increase the risk of infant mortality. Therefore, we performed a meta-analysis to systematically assess the association between maternal BMI and the risk of infant mortality. Methods: Two investigators systematically searched Pubmed, Embase database, and Cochrane Library from inception to November 26, 2020, without language restrictions. In parallel, a dose-response was assessed. Results: Finally, 22 cohort studies included in this paper with a total of 13,532,293 participants showed that maternal overweight would significantly increase the risk of infant mortality (RR 1.16,95%CI1.13-1.19), neonatal mortality (RR1.23,95%CI1.08-1.39), early neonatal mortality (RR1.55,95%CI1.26-1.92) and post-neonatal mortality (RR1.18,95%CI 1.07-1.29) compared to normal BMI. Similarly, maternal overweight would significantly increase the risk of infant mortality (RR1.55,95%CI1.41-1.70), neonatal mortality (RR1.55,95%CI1.28-1.67), early neonatal mortality (RR1.37,95%CI1.13-1.67), and post-neonatal mortality (RR1.30,95%CI1.03-1.65), whereas maternal underweight might tend to decrease the risk of infant mortality(RR 0.93,95%CI0.88-0.98). In a dose-response analysis, the risk of infant mortality was significantly increased when maternal BMI was greater than 25 kg/m2. Conclusions: Maternal overweight or obesity significantly increased the risk of infant mortality, neonatal mortality, early neonatal mortality, and post-neonatal mortality compared to normal BMI, with a dose-dependent relationship. Besides, maternal underweight does not increase the risk of infant mortality, neonatal mortality, early neonatal mortality, and postneonatal mortality, but rather tended to decrease the risk of infant mortality. Early weight management may provide potential benefits to infants, and more prospective studies with large samples are needed to verify this finding in the future.